1996
DOI: 10.1097/00002060-199601000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cognitive Impairment on Rehabilitation Outcome1

Abstract: Previous studies examining the relationship between cognition and ability to benefit from inpatient rehabilitation have found cognitive dysfunction to be associated with a poor rehabilitation outcome. To examine whether cognitive dysfunction precluded effective rehabilitation, 52 consecutive admissions to a geriatric rehabilitation unit were assigned Mini Mental State Examination (MMSE) scores. Functional gains were assessed by the change in Functional Independence Measure (FIM) score from admission to dischar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
64
2
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(80 citation statements)
references
References 5 publications
11
64
2
3
Order By: Relevance
“…Preliminary evidence indicates that this care program assisted with allowing older adults to continue living in the community. This is in contrast to previous research by Diamond et al (1996) and Lenze et al (2004), who found that patients with CI were more likely to be discharged to a nursing home. The most probable reason for patients not being discharge to a nursing home is the expectation made clear to family members and patients at admission that the patients will be going back to their home.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Preliminary evidence indicates that this care program assisted with allowing older adults to continue living in the community. This is in contrast to previous research by Diamond et al (1996) and Lenze et al (2004), who found that patients with CI were more likely to be discharged to a nursing home. The most probable reason for patients not being discharge to a nursing home is the expectation made clear to family members and patients at admission that the patients will be going back to their home.…”
Section: Discussioncontrasting
confidence: 99%
“…These differences, which were not statistically significant, are attributable to the fact that CI patients were, on average, on the rehabilitation unit for 3 days less than patients with intact cognition prior to being discharged home. This result was not expected, as previous research has found the opposite: patients with CI usually have longer LOS than those who are cognitively intact (Diamond et al, 1996;Moncada et al, 2006), and patients with CI usually have lower rehabilitation efficiency scores than those patients who are intact (Heruti et al, 1999).…”
Section: Discussionmentioning
confidence: 68%
“…However, it has been reported that geriatric patients with higher FIM social cognitive items are more often discharged home. 30 Diamond et al 31 indicate that geriatric patients with cognitive dysfunction should be considered for rehabilitation if functional gains will affect their quality of life. It is also important to note that patients of geriatric rehabilitation units classified as depressed at discharge have lower FIM scores at admission and at discharge.…”
Section: Discussionmentioning
confidence: 99%
“…20 Cognitive impairment is associated with a Timely discharge of older patients from hospital poorer outcome from rehabilitation, although some patients with significant cognitive impairment do return home following appropriate rehabilitation. 21 It is reasonable in cases of uncertainty to obtain advice from a member of the geriatric MDT.…”
Section: Do Not Assume That All Older Patients Require Rehabilitationmentioning
confidence: 99%